Sleep patterns in patients treated for non-secreting intra- and parasellar tumors: A self-report case-control study - Wild, Carl Mathis; Stieg, Mareike; Stalla, Günter K.; Jung-Sievers, Caroline; Auer, Matthias K.; Athanasoulia-Kaspar, Anastasia P. (Frontiers in Endocrinology, 2022)
Purpose: In this study we evaluate sleep patterns of patients treated for non-secreting intra- and parasellar tumors and age- and sex-matched healthy controls. Methods: We conducted a self-report cross-sectional case-control study with 104 patients treated for non-secreting intra- and parasellar tumors and 1800 healthy controls in an 1:8 matching. All subjects answered the Munich ChronoType Questionnaire, whereas patients were provided the Pittsburgh Sleep Quality Index, the Epworth Sleepiness Scale, the Short-Form 36 Health survey, the Beck Depression Inventory and the State-Trait Anxiety Inventory additionally. Results: Patients treated for non-secreting intra- and parasellar tumors go to bed earlier, fall asleep earlier, need less time to prepare to sleep but also to get up. Additionally, they lie and sleep. The subgroup analysis showed that patients with secondary adrenal insufficiency compared to controls experienced shorter daily light exposure and longer sleep latency. Higher hydrocortisone dose (>20mg) was associated with worse score in global, physical and mental health, shorter time to prepare to sleep, earlier sleep onset and longer sleep duration. Conclusion: Our study shows that patients treated for non-secreting intra- and parasellar tumors, even if successfully treated, experience altered sleep patterns compared to controls. We suggest that managing clinicians should enlighten these possible sleep alterations to their patients and use specific questionnaires to document sleep disturbances. Additionally, when treating patients surgically, especially by transcranial approach, damaging the suprachiasmatic nucleus should be avoided. Furthermore, circadian hydrocortisone replacement therapy ideally with dual-release hydrocortisone - if possible, in a dose not more than 20mg daily - that resembles physiological cortisol levels more closely may be beneficial and could improve sleep patterns and sleep-related quality of life.